Preparation method and application of light-colored nanoparticulate lignin
By treating flax stalks with glyoxylic acid and p-toluenesulfonic acid, light-colored nanoparticle lignin with low condensation degree was prepared, which solved the problems of dark color and insufficient ultraviolet absorption performance of lignin in the existing technology and achieved a highly efficient sun protection effect.
Patent Information
- Application Number
- CN202311133223.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-11-04
- Estimated Expiration
- 2043-09-04
AI Technical Summary
Existing technologies make it difficult to prepare lignin with light color and high UV absorption properties, which limits its application in sunscreens.
A mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid was used to treat flax stalks. The formation of C-C bonds between benzene rings in lignin was inhibited by the acetal reaction of glyoxylic acid with lignin, and light-colored nanoparticle lignin with low condensation degree was prepared and applied to sunscreen.
The prepared light-colored nanoparticle lignin significantly improves the UV protection effect in sunscreens, with an SPF value of up to 58.43. Moreover, the process is simple and the raw materials can be recycled.
Smart Images

Figure CN116987284B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of high-value utilization of lignin, and particularly relates to a preparation method and application of light-colored nano-particle lignin. BACKGROUND
[0002] The statements herein are provided only to complement the background of the present application and are not necessarily indicative of the prior art.
[0003] Lignin is widely present in lignocellulosic biomass, and is abundant and renewable on earth. Lignin contains some functional groups that can absorb ultraviolet rays, such as phenols, ketones and conjugated double bonds. In addition, lignin has been proved to be non-cytotoxic and good biocompatibility. These unique advantages enable lignin to be used to produce environmentally friendly and safe functional lignin-based products, such as sunscreen.
[0004] It is known that due to different separation and extraction conditions of lignin, the color of the obtained lignin varies greatly. Taking the most common pulping black liquor lignin as an example, under harsh pulping conditions, lignin undergoes severe condensation, making its color tend to be black, which seriously limits the application range of lignin. Therefore, when lignin is applied to sunscreen, its staining behavior on human skin must be considered to avoid its color polluting the skin, so as to be accepted by the general consumers.
[0005] Some researchers have improved the color of pulping black liquor lignin by solvent fractionation and acetylation treatment, and evaluated its sunscreen effect. After acetylation, the free phenolic hydroxyl group of lignin is blocked, and the formation of quinone structure is reduced. Although this method improves the color of lignin, it inevitably reduces the ultraviolet light absorption capacity of lignin. The prepared lignin-based sunscreen can only meet the daily requirements of consumers when the lignin content (8 wt.%) is high. Some researchers also use organic solvents (methanol, ethanol and acetone) or ultrafiltration membrane to fractionate alkali lignin to obtain lignin with low molecular weight and light color to prepare lignin-based sunscreen. Although these molecular weight fractionation methods can obtain lignin with lighter color and lower molecular weight, the use of chemicals is increased or the proportion of low molecular weight lignin obtained is very small, resulting in poor sunscreen effect of lignin, which is difficult to meet the requirements. SUMMARY
[0006] In view of the deficiencies of the prior art, the purpose of the present application is to provide a preparation method and application of light-colored nano-particle lignin, and to realize the high-value utilization of kenaf stem resources.
[0007] In order to achieve the above-mentioned purpose, the present application is realized by the following technical solutions:
[0008] In a first aspect, the present application provides a method for preparing light-colored nanoparticle lignin, comprising the following steps: washing and grinding the peeled jute stalk into powder, and then adding the powder into a mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid for reaction, wherein the concentration of glyoxylic acid is 5-8 wt.%, the concentration of p-toluenesulfonic acid is 50-80 wt.%, the reaction temperature is 70-100℃, and the reaction time is 30-60 min;
[0009] After the reaction is completed, solid-liquid separation is performed, the filtrate is precipitated with water to deposit lignin, and the lignin is dialyzed and freeze-dried to obtain light-colored jute lignin.
[0010] The light-colored jute lignin is dissolved in a γ-valerolactone solution, dialyzed with ultrapure water, and then freeze-dried to obtain light-colored nanoparticle lignin.
[0011] In the related research on the extraction of light-colored lignin from jute stalks, the inventors tried to use a mixed aqueous solution of formaldehyde / p-toluenesulfonic acid to treat the powdered particles of jute stalks to extract lignin from jute. After water washing and dialysis, light-colored lignin nanospheres were obtained. Adding a small amount of the light-colored lignin to existing sunscreen products can significantly improve the sunscreen effect. For example, the SPF value of a commercial sunscreen lotion with an SPF of 10 (the actual measured SPF value is about 7) can be increased to 20.42 after adding 3% of the light-colored lignin nanospheres. When the amount of the light-colored lignin nanospheres is increased to 4%, the SPF value can reach 27.84.
[0012] Further research by the inventors found that the condensation degree of the light-colored lignin extracted by the mixed aqueous solution of formaldehyde / p-toluenesulfonic acid is relatively large, which results in a small proportion of low molecular weight lignin, thereby limiting the further improvement of the sunscreen effect.
[0013] Therefore, the inventors sought to find an extraction solution that can reduce the condensation degree of lignin and further optimize the extraction method. After a series of experiments, it was found that when a mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid is used to extract lignin from jute stalks, the glyoxylic acid reacts with lignin to form an acetal, which avoids the formation of C-C bonds between the benzene rings of lignin, effectively inhibits the condensation of lignin, and thus obtains lignin with a low condensation degree. The low molecular weight lignin has a light color and significantly improves its ultraviolet absorption performance. The SPF value of a commercial sunscreen lotion with an SPF of 10 (the actual measured SPF value is about 7) can be increased to 37.68 after adding 3% of the light-colored nanoparticle lignin extracted by this method. When the amount of the light-colored nanoparticle lignin is increased to 4%, the SPF value can reach 58.43.
[0014] The main role of p-toluenesulfonic acid is to degrade and dissolve lignin in jute rods, and glyoxylic acid also has a certain effect on the dissolution of lignin in jute rods.
[0015] In some embodiments, the particle size of the Kenaf stem powder is 20-40 mesh.
[0016] In some embodiments, the mass of the Kenaf stem powder added to 1 liter of the mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid is 40-200 g.
[0017] In some embodiments, the concentration of glyoxylic acid in the mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid is 5-8 wt.%, and the concentration of p-toluenesulfonic acid is 50-80 wt.%, and
[0018] Preferably, the concentration of glyoxylic acid in the mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid is 6 wt.%.
[0019] In some embodiments, water is added to reduce the concentration of p-toluenesulfonic acid in the filtrate to 9-11 wt.% to precipitate lignin. Preferably, the concentration of p-toluenesulfonic acid is reduced to 10 wt.%.
[0020] Preferably, the time for precipitating lignin by adding water is at least 24 h.
[0021] In some embodiments, the method for preparing the light-colored nanoparticulate lignin comprises dissolving the light-colored lignin in a 90-99 wt.% γ-valerolactone solution, dialyzing in ultrapure water, and then freeze-drying to obtain the light-colored nanoparticulate lignin.
[0022] In a second aspect, the present application provides a sunscreen emulsion to which the light-colored nanoparticulate lignin is added. The amount of the light-colored nanoparticulate lignin added is 1-4 wt.%.
[0023] The beneficial effects achieved by one or more embodiments of the present application are as follows:
[0024] (1) The present application provides a method for extracting light-colored lignin from Kenaf stems. The extracted lignin has a low degree of condensation, a light color, and good ultraviolet absorption properties.
[0025] (2) The present application provides a method for preparing light-colored nanoparticulate lignin and applying it to sunscreen. The prepared sunscreen has good ultraviolet protection ability and biocompatibility.
[0026] (3) The Kenaf stem raw material used in the present application is an agricultural waste, and the extraction is performed using an aqueous solution of glyoxylic acid / p-toluenesulfonic acid. The process is simple, the reaction conditions are mild, and the reagent p-toluenesulfonic acid can be recycled. BRIEF DESCRIPTION OF DRAWINGS
[0027] The accompanying drawings, which form a part of the present application, are used to provide a further understanding of the present application, and the illustrative embodiments thereof, and are not intended for use in limiting the present application.
[0028] Figure 1 is a photo of the appearance of the light-colored lignin extracted from the Kenaf stalks of the present application;
[0029] Figure 2 is a UV absorption intensity curve of the light-colored lignin extracted from the Kenaf stalks of the present application;
[0030] Figure 3 is a SEM image of the light-colored lignin nanoparticles prepared in the present application;
[0031] Figure 4 is a particle size distribution graph of the light-colored lignin nanoparticles prepared in the present application;
[0032] Figure 5 is a photo of the appearance of the lignin-based sunscreen prepared in the present application;
[0033] Figure 6 is a photo of the appearance of the lignin-based sunscreen prepared in the present application applied to human skin;
[0034] Figure 7 is a UV transmittance curve of the lignin-based sunscreen prepared in the present application;
[0035] Figure 8 is a measured value of the sun protection factor (SPF) of the lignin-based sunscreen prepared in the present application. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed description is illustrative only, and is intended to provide further description of the application. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0037] The present application is further described below in conjunction with examples.
[0038] Example 1: Extraction Example
[0039] The Kenaf stalks after peeling were washed clean and air-dried, and were ground into powder particles using a mechanical method. 3.0 g of the raw material particles of 20-40 mesh were placed in a conical flask, 50 mL of the prepared glyoxylic acid / p-toluenesulfonic acid aqueous solution (the concentration of glyoxylic acid was 6 wt.%, and the concentration of p-toluenesulfonic acid was 60 wt.%) was added, and the conical flask was placed in a water bath at 70°C for stirring reaction for 30 min after pre-soaking for 30 min at room temperature.
[0040] After the reaction was completed, solid-liquid separation was performed using a suction filtration device, the filtrate was transferred to a beaker, ultrapure water was added to reduce the concentration of p-toluenesulfonic acid in the filtrate to 10 wt.%, and the filtrate was left still for 24 h, the lignin was deposited, the supernatant was removed, and the deposited lignin was dialyzed to neutral in ultrapure water, and then freeze-dried to obtain the light-colored lignin.
[0041] Example 2: Extraction Example
[0042] The peeled kenaf stalks were washed clean and air-dried, and were ground into powder particles by mechanical method. 3.0 g of 20-40 mesh raw material particles were placed in a conical flask, 50 mL of prepared glyoxylic acid / p-toluenesulfonic acid aqueous solution (the concentration of glyoxylic acid was 6 wt.%, and the concentration of p-toluenesulfonic acid was 50 wt.%) was added, and the conical flask was placed in a water bath at 80°C for stirring reaction for 30 min after pre-impregnation for 30 min at room temperature.
[0043] After the reaction was completed, solid-liquid separation was performed by using a suction filtration device, the filtrate was transferred to a beaker, ultrapure water was added to reduce the concentration of p-toluenesulfonic acid in the filtrate to 10 wt.%, and the mixture was left still for 24 h to deposit lignin. The supernatant was removed, and the deposited lignin was dialyzed to neutral in ultrapure water, and then freeze-dried to obtain light-colored lignin.
[0044] Example 3: Extraction Example
[0045] The peeled kenaf stalks were washed clean and air-dried, and were ground into powder particles by mechanical method. 3.0 g of 20-40 mesh raw material particles were placed in a conical flask, 50 mL of prepared glyoxylic acid / p-toluenesulfonic acid aqueous solution (the concentration of glyoxylic acid was 6 wt.%, and the concentration of p-toluenesulfonic acid was 60 wt.%) was added, and the conical flask was placed in a water bath at 80°C for stirring reaction for 30 min after pre-impregnation for 30 min at room temperature.
[0046] After the reaction was completed, solid-liquid separation was performed by using a suction filtration device, the filtrate was transferred to a beaker, ultrapure water was added to reduce the concentration of p-toluenesulfonic acid in the filtrate to 10 wt.%, and the mixture was left still for 24 h to deposit lignin. The supernatant was removed, and the deposited lignin was dialyzed to neutral in ultrapure water, and then freeze-dried to obtain light-colored lignin.
[0047] Example 4: Extraction Example
[0048] The peeled kenaf stalks were washed clean and air-dried, and were ground into powder particles by mechanical method. 3.0 g of 20-40 mesh raw material particles were placed in a conical flask, 50 mL of prepared glyoxylic acid / p-toluenesulfonic acid aqueous solution (the concentration of glyoxylic acid was 6 wt.%, and the concentration of p-toluenesulfonic acid was 70 wt.%) was added, and the conical flask was placed in a water bath at 80°C for stirring reaction for 30 min after pre-impregnation for 30 min at room temperature.
[0049] After the reaction was completed, solid-liquid separation was performed by using a suction filtration device, the filtrate was transferred to a beaker, ultrapure water was added to reduce the concentration of p-toluenesulfonic acid in the filtrate to 10 wt.%, and the mixture was left still for 24 h to deposit lignin. The supernatant was removed, and the deposited lignin was dialyzed to neutral in ultrapure water, and then freeze-dried to obtain light-colored lignin.
[0050] Photographs of the appearance of light-colored lignin from red hemp stalks in Examples 1-4 are shown below. Figure 1 As shown in the figure, C represents the concentration of p-toluenesulfonic acid, T represents the reaction temperature, and t represents the reaction time. The figure shows that the extracted light-colored lignin from flax stalks has a pale yellow appearance. This is attributed to the acetal reaction between glyoxylic acid and lignin, which avoids the formation of C-C bonds between the benzene rings of lignin, thus obtaining lignin with a low degree of condensation and a light color.
[0051] The UV absorption curve of the extracted light-colored lignin from flax stalks is as follows: Figure 2 As shown, it has good UV absorption intensity in the ultraviolet region, and the light-colored lignin extracted under mild conditions has even higher UV absorption intensity.
[0052] Example 5: Application Example
[0053] The light-colored lignin extracted from flax tung oil in Example 2 was dissolved in 98 wt.% γ-valerol solution at a concentration of 0.4 mg / mL. The solution was dialyzed in ultrapure water at room temperature for at least 48 h, followed by freeze-drying to obtain light-colored nanoparticle lignin, labeled GA-LNPs. Its SEM images and particle size distribution are shown below. Figure 3 and Figure 4 As shown, the lignin nanoparticles are in the shape of regular spheres.
[0054] Light-colored nanoparticle lignin was mixed with commercial SPF 10 sunscreen lotion at mass fractions of 1%, 2%, 3%, and 4%, respectively, and stirred thoroughly (500 rpm) for 24 hours in the dark to obtain lignin-based sunscreens with different lignin contents, such as... Figure 5 As shown in the figure, the mixed sunscreen lotion exhibits minimal color change compared to the blank sample, remaining a light yellow. When applied to human skin, as... Figure 6 As shown, no obvious staining behavior was observed.
[0055] UV transmittance tests were conducted on samples of lignin-based sunscreens and commercial sunscreens, such as... Figure 7 As shown, with the increase of lignin addition, the UV transmittance of the sunscreen in the UVA (320nm-400nm) and UVB (290nm-320nm) regions decreased significantly, indicating that the light-colored nano-particle lignin played a good role in UV protection in the sunscreen.
[0056] The sun protection factor (SPF) of lignin-based sunscreens and commercial sunscreens is calculated based on ultraviolet transmittance, such as... Figure 8The results show that the SPF values of the lignin-based sunscreen creams prepared by adding 2wt.%, 3wt.% and 4wt.% GA-LNPs into SPF10 sunscreen cream can reach 15.66, 37.68 and 58.43, respectively, which exceed the SPF15, SPF30 and SPF50 sunscreen products commonly seen in the market, and thus the lignin-based sunscreen cream prepared can fully meet the daily sunscreen needs of people.
[0057] The preferred embodiments of the present application have been described above with the aid of drawing figures, and are not intended to limit the present application, and for those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for extracting light-colored nanoparticle lignin, characterized in that: The process includes the following steps: washing and grinding the peeled flax stalks into powder, then adding the powder to a mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid for reaction. The concentration of glyoxylic acid is 5-8 wt.%, the concentration of p-toluenesulfonic acid is 50-80 wt.%, the reaction temperature is 70-100 ℃, and the reaction time is 30-60 min. After the reaction was completed, the solid and liquid were separated. The filtrate was hydrated and lignin was deposited. The lignin was then dialyzed and freeze-dried to obtain light-colored kenaf lignin. Light-colored lignin from kenaf was dissolved in γ-valerol solution, dialyzed with ultrapure water, and then freeze-dried to obtain light-colored nano-particle lignin. During the sedimentation process of adding water to the filtrate, the amount of p-toluenesulfonic acid in the filtrate is reduced to 9-11 wt.%, and lignin is deposited.
2. The method for extracting light-colored nanoparticle lignin according to claim 1, characterized in that: The particle size of the sesame stalk powder is 20-40 mesh.
3. The method for extracting light-colored nanoparticle lignin according to claim 1, characterized in that: The mass of 40-200g of sesame stalk powder is added to every 1 liter of a mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid.
4. The method for extracting light-colored nanoparticle lignin according to claim 1, characterized in that: In the mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid, the concentration of glyoxylic acid is 5-8 wt.%.
5. The method for extracting light-colored nanoparticle lignin according to claim 4, characterized in that: In the mixed aqueous solution of glyoxylic acid and p-toluenesulfonic acid, the concentration of p-toluenesulfonic acid is 50-80 wt.%.
6. The method for extracting light-colored nanoparticle lignin according to claim 1, characterized in that: The deposition time for lignin is at least 24 hours.
7. The method for extracting light-colored nanoparticle lignin according to claim 1, characterized in that: Light-colored lignin was dissolved in a 90-99 wt.% γ-valerol solution, dialyzed in ultrapure water for at least 48 h, and then freeze-dried to obtain light-colored nanoparticle lignin.
8. A light-colored nanoparticle lignin, characterized in that: Prepared by any of the extraction methods described in claims 1-7.
9. A sunscreen lotion, characterized in that: The product contains the light-colored nanoparticle lignin as described in claim 8, wherein the amount of light-colored nanoparticle lignin added is 1-4 wt.%.
Citation Information
Patent Citations
Light-colored kenaf lignin nano spherical particles as well as preparation method and application thereof
CN115322400A